Let's Play Tinder! Aesthetics of a Dating App - Maria Garda; Veli-Matti Karhulahti (United States, 2022)
This article provides an analysis of the “dating app” Tinder as an aesthetic ludic artifact. By scrutinizing the title’s features of gameplay and expressive–interpretive social interaction, Tinder usage is set into a frame theory context and shown to operate by multiple overlapping frames that allow romantic engagement to be entered as play and vice versa.